An investigation of MMC based DC/DC converter for HVDC grids - Song, Wenping (2018)
The interconnection of multiple oshore renewable energy sources to form a network and maximise their availability requires a method for controlling the transportation of bulk electrical energy. For the distances considered, and as a result of the capacitive nature of HVAC cables, HVDC is the most likely technology for meeting these bulk transport requirements.